Determinants of sertu cleansing integrity in Halal logistics operations in Malaysia / Noorsiah Ahmad - Ahmad, Noorsiah (Institute of Graduate Studies, UiTM, 2018)
The motive for halal logistics is to assure integrity of halal product and maintaining the halal status throughout the supply chain from the halal certified manufacturers and to the consumers. When a halal product comes into physical contact with a non-halal substance or cross contamination occurs during the transport and logistics delivery, the halal product becomes non-halal. Non halal product is haram product contaminated with "filth" or najs which affect human consumption or use. Thus sertu cleansing operations is to ensure transport and logistics carrying halal product are assured with no occurrence of contamination. Sertu cleaning is not merely cleansing or cleaning dirt or filth, it is an act of "purification" and assurance of health and hygiene with shariah values. There is a gap and weakness to guarantee assurance of halal integrity of halal product along the supply chain as transporters and logistics service providers are not fully aware of mitigation controls and effects on cross contamination; the requirements and compliance for sertu cleansing in their operations; and assurance of tracking and traceability of logistics delivery. Additionally, the integrity element in sertu cleansing has yet to be explored due to lack of study. Therefore, this study attempts to investigate on determinants in sertu cleansing integrity in transport operations for halal logistics in Malaysia with reference to the Malaysia Standards MS2400: 2010…